Role of community participation in community development (Anhurological study of the nation Hospital in the city of salhab) (Damascus University Journal of arts and humanities sciences, 2021)
The importance of the study is to highlight the areas of the health of health services and because the state today in a war. It needs to help reconstruction of the country. Where popular voluntary contributions and voluntary work in the community in the city of downtown to activate community participation in the construction of a national hospital that serves the region needed for the services.The goal of research has identified the role of cultural contrast among the community of participating community in the construction of the national hospital in the development of the community participation process and identifies the most important indicators that can be relied upon in the measure of community participation.The relevant transparent approach was relyed in the observation of the participation in the view of the participation in the observation of the participation in the construction of the national community in the construction of the nation hospital as a volunteer at work.The research finds several results in the most important of which had led to community participation to the intellectuals of the community of society to achieve objectives to achieve them a common collective interests and increased the process of participation from planting and promoting some moral values that seek to improve humanitarian thinking through the development of a generation seeking to review the community building and assistance in the reconstruction plans of the country.
Keywords: Role of community participation in community development (Anhurological study of the nation Hospital in the city of salhab)